Optimization of drawing sequence in longwall top coal caving mining through an FDM‐DEM model - Yuming Huo; Shaozhuo Wang; Defu Zhu; Zhonglun Wang (Energy Science & Engineering)
Abstract The Longwall top coal caving (LTCC) technology is regarded as one of the most crucial approaches for exploiting thick coal seams. A crucial and effective approach for improving the recovery rate of top coal and reducing coal resource losses in LTCC faces is to reasonably select process parameters based on actual mining and geological conditions of different mines. The main focus of this paper is the engineering background of the 12,309 LTCC face in Wangjialing Coal Mine. A numerical model is developed using FALC3D and PFC3D software, employing a finite difference method and discrete element method. This model takes into account predetermined cutting and caving ratios, as well as drawing intervals. To examine the caving process and roof particles, three different drawing sequences were examined: sequential drawing, segmented sequential drawing, and intermittent drawing. The findings suggest that, in terms of the reset shape of the drawing body before individual and entire caving, the segmented sequential drawing method exhibits noticeable drawbacks compared to the other two methods. From the perspective of the drawing weight, following “closing drawing opening when seeing gangue”, the sequential drawing, segmented sequential drawing, and intermittent drawing methods can yield 32.42 t, 26.87 t, and 35.78 t of top coal, with corresponding recovery rates of 73.39%, 60.81%, and 82.97%. Therefore, it can be concluded that intermittent drawing is suitable for implementation on LTCC working face 12,309.